Pre-training competencies and the productivity of apprentices - Jansen, Anika [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2017)
"The purpose of this paper is to investigate the relationship between pre-training competencies of apprentices and their productivity at the workplace. For our analysis, we use firm-level data on apprentices' oral and writing competencies and competencies in basic mathematics, information technology, and problem solving. We regress the apprentices' productivity on these school competencies and include a number of firm and apprentice-specific control variables. By reducing our dataset to firms that only have one apprentice we transform the firm-level data into quasi individual-level data. The main findings are that not all competencies are equally related to productivity. Problem-solving competencies followed by oral and writing competencies show the strongest relation to the productive potential of apprentices. IT competencies are also positively but weakly related to the apprentices' productivity. In contrast, higher levels of basic mathematical competencies leave productivity levels largely unchanged. Differentiating between occupational groups, we find that the positive relation between the competencies and productivity predominantly exists in commercial occupations rather than in industrial and technical occupations." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 2.3 Auszubildende; Betriebliche Berufsausbildung; Auszubildender; Grundbildung; Kommunikationsfähigkeit; Schreibkompetenz; Mathematische Grundbildung; Informationstechnische Bildung; Problemlösen; Einflussfaktor; Produktivität